Libyan EFL Undergraduates’ Motivation Toward Integrating Improv Cards with Role-Play Technique in English Speaking Classes (International Journal of Language, Literacy and Translation, 2024)
The primary objective of the study is to measure learners’ perceptions of how integrating Improv Cards with Role-Playing Techniques into the EFL curriculum can enhance students' motivation to engage in spoken English communication and influence their attitudes toward language learning. Data were collected through a questionnaire administered to a sample of Libyan undergraduate students enrolled in EFL courses. The questionnaire included items related to students' motivation levels towards speaking English and their experiences with the use of Improv Cards activities. Despite the challenges, the students were excited to participate in class activities and enjoyed using Improv Cards for role-play, which made them more eager to speak English. This approach significantly increased their motivation, as revealed by the findings. Moreover, the participants demonstrated more favourable beliefs towards language learning, emphasizing the practical relevance of the role-playing exercises in improving their communication skills. The results suggest that incorporating Improv Cards with role-playing techniques into EFL instruction can be a valuable pedagogical approach for enhancing students' motivation and attitudes towards speaking English. Educators and curriculum designers should consider integrating such interactive activities to foster a more positive and engaging learning environment. Furthermore, this study provides insights into the effectiveness of innovative language teaching methods and their potential to promote effective communication skills in EFL contexts, which can be applied beyond Libya to benefit language learners worldwide.